BIOLOGY OF THE HILSA, HILSA ILISHA (HAMILTON) OF THE RIVER HOOGHLY - Pillay, T.V.R. (Indian Journal of Fisheries, 2016)
Sharp fluctuations in the abundance of Hilsa and reports of widespread decline in its fisheries have focussed attention on the problem of the biology of Hilsa. A detailed study of the magnitude and dynamics of Hilsa populations has now become essential to assess. the state of its fisheries and to formulate adequate management measures for the conservation and maintenance of this important resource. Unfortunately the information now available is too meagre to be of help in such investigations. Moreover, in view of the possible existence of diff'erent stocks of Hilsa in Indian waters, it is not known how far the inferences regarding the bionomics of the fish in a particular area would be applicable in another area.